Growth, development, and phenotypic spectrum of individuals with deletions of 2q33.1 involving SATB2. Issue 4 (13th January 2021) - Zarate, Yuri A.; Bosanko, Katherine A.; Thomas, Mary Ann; Miller, David T.; Cusmano‐Ozog, Kristina; Martinez‐Monseny, Antonio; Curry, Cynthia J.; Graham, John M.; Velsher, Lea; Bekheirnia, Mir Reza; Seidel, Veronica; Dedousis, Demitrios; et al.
Abstract: SATB2 ‐Associated syndrome (SAS) is an autosomal dominant, multisystemic, neurodevelopmental disorder due to alterations in SATB2 at 2q33.1. A limited number of individuals with 2q33.1 contiguous deletions encompassing SATB2 (ΔSAS) have been described in the literature. We describe 17 additional individuals with ΔSAS, review the phenotype of 33 previously published individuals with 2q33.1 deletions ( n = 50, mean age = 8.5 ± 7.8 years), and provide a comprehensive comparison to individuals with other molecular mechanisms that result in SAS (non‐ΔSAS). Individuals in the ΔSAS group were often underweight for age (20/41 = 49%) with a progressive decline in weight (95% CI = −2.3 to −1.1, p < 0.0001) and height (95% CI = −2.3 to −1.0, p < 0.0001) Z‐score means from birth to last available measurement. ΔSAS individuals were often noted to have a broad spectrum of facial dysmorphism. A composite image of ΔSAS individuals generated by automated image analysis was distinct as compared to matched controls and non‐ΔSAS individuals. We also present additional genotype–phenotype correlations for individuals in the ΔSAS group such as an increased risk for aortic root/ascending aorta dilation and primary pulmonary hypertension for those individuals with contiguous gene deletions that include COL3A1 / COL5A2 and BMPR2, respectively. Based on these findings, we provide additional care recommendations for individuals with ΔSAS variants. Abstract :